Safety and Tolerability of Cariprazine in Patients with Schizophrenia: A Pooled Analysis of Eight Phase II/III Studies - Barabássy, Ágota (Neuropsychiatr Dis Treat, 2021)
BACKGROUND: Long-term treatment with antipsychotic agents is indicated for patients with schizophrenia, but treatment is associated with adverse events (AEs) that contribute to medication discontinuation and nonadherence. Understanding drug safety profiles is critical to avoid unwanted side effects. Cariprazine is a potent dopamine D(3)/D(2) receptor partial agonist that is approved for the treatment of adults with schizophrenia (EU, US) and acute manic/mixed and depressive episodes associated with bipolar I disorder (US). METHODS: Post hoc analyses were conducted to characterize the safety profile of cariprazine within the recommended 1.5–6 mg/d dose range for schizophrenia; data from 8 short- or long-term clinical trials were analyzed. RESULTS: In the pooled cariprazine-treated safety population (n=2048), the rate of study completion was 52.8%, with withdrawal of consent, insufficient response, and AEs the most common reasons for premature discontinuation. The most commonly reported AEs (>10%) in the overall cariprazine-treatment group were akathisia (14.6%), insomnia (14.0%), and headache (12.1%); most AEs were considered mild (71.0%) or moderate (26.5%). Most akathisia was mild/moderate (97.5%) and >93% of patients remained on treatment; akathisia events were managed by rescue medications (56.3%) or dose reduction (18.3%). The metabolic profile of cariprazine was neutral in patients with short- and long-term exposure; mean weight gain was 1 kg for overall cariprazine, with an AE of weight increased reported for 5.1%. Other AEs of special interest that occurred at >3% for overall cariprazine were extrapyramidal disorder (7.0%), sedation (3.7%), and somnolence (3.1%); prolactin elevation, cognition impairment, sexual dysfunction, suicidality, and QT prolongation occurred at ≤1%. CONCLUSION: Akathisia, the most common cariprazine-related AE, was mild/moderate and resulted in few study discontinuations; symptoms were well managed and most patients remained on treatment. Results of this analysis indicated that cariprazine in the recommended dose range was safe and generally well tolerated in patients with schizophrenia. TRIAL REGISTRATION: Studies registered with ClinicalTrials.gov (NCT00404573, NCT01104779, NCT00694707, NCT01104766, NCT01104792, NCT00839852, and NCT01412060) and EudraCT (2012–005485-36).